Foreign workers in Canada: Labour force attachment among temporary residents with paid employment in 2019 - Yuqian Lu; Garnett Picot (Economic and Social Reports)
Temporary residents constitute an important supply of labour for the Canadian economy. However, some of them do not work in a given year, even when holding a valid work permit. This article estimates the share of temporary residents who had paid employment but were “weakly attached” to the Canadian labour market in 2019.